Two new species of Anaphes Haliday (Hymenoptera: Mymaridae) from India and Indonesia - Anwar, Prince Tarique; Zeya, Shahid Bin; Huber, John T. (Zootaxa, 2019)
Two species of Anaphes Haliday with distinctive females are described from India (A. triapitsyni Anwar & Zeya, sp. nov.) or from India and Indonesia (A. kailashchandrai Anwar & Zeya, sp. nov.). The only other Anaphes species known to occur in India is A. quinquearticulatus Huber & Triapitsyn because previous records of A. pallipes (Ashmead) and A. pullicrurus (Girault) are based on misidentifications. These latter two names are therefore removed from the faunal list of India. An illustrated key to females of the three described species of Anaphes known from India is given. The described species of Anaphes known from Australia are also briefly reviewed, with type material of four previously unillustrated species being newly imaged and compared to the Indian species.